1991
DOI: 10.2527/1991.6941607x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in metabolites, metabolic hormones, and luteinizing hormone before puberty in Angus, Braford, Charolais, and Simmental heifers.

Abstract: We determined changes in insulin, glucose, free fatty acids (FFA), growth hormone (GH), insulin-like growth factor I (IGF-I) and LH before puberty in Angus, Braford, Charolais, and Simmental heifers. Our primary objective was to identify metabolites and metabolic hormones that serve as metabolic cues for onset of puberty. Angus (n = 12). Braford (n = 7), Charolais (n = 9), and Simmental (n = 7) heifers were assigned at weaning (289 +/- 25 d of age; 264 +/- 23 kg) to open-sided pens with slotted floors, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
1
7

Year Published

1992
1992
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 0 publications
1
35
1
7
Order By: Relevance
“…This would have resulted in a change in the ratio between IGFBP-3 and IGF-1, and suggests that variation in IGF-1: IGFBP-3 ratio could possibly mediate the time to reach puberty. Results obtained by Jones et al (1991), Granger et al (1989) and Yelich et al (1996) differ from results obtained in the present experiment in terms of association between puberty and IGF-1 concentration. These authors found that IGF-1 increased before puberty, independent of dietary treatment.…”
Section: Discussioncontrasting
confidence: 57%
“…This would have resulted in a change in the ratio between IGFBP-3 and IGF-1, and suggests that variation in IGF-1: IGFBP-3 ratio could possibly mediate the time to reach puberty. Results obtained by Jones et al (1991), Granger et al (1989) and Yelich et al (1996) differ from results obtained in the present experiment in terms of association between puberty and IGF-1 concentration. These authors found that IGF-1 increased before puberty, independent of dietary treatment.…”
Section: Discussioncontrasting
confidence: 57%
“…In contrast with insulin secretion, plasma IGF-I concentrations increased during the onset of puberty in Shiba goats, as shown in a variety of species such as rodents [34,35], ruminants [22,36], and primates [37,38] including humans [37][38][39][40]. IGF-I concentrations in the circulation are closely associated w ith nutritional status in both monogastric animals [21] and ruminants [22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Serum IGF-I was assayed using glycylglycine hydrochloride extraction procedures as described (24) with modifications (25,26). The standard source was recombinant human IGF-I (Amgen, Thousand Oaks, CA).…”
Section: Methodsmentioning
confidence: 99%
“…Serum INS concentrations were analyzed via the procedures of Hales and Randle (27) with modifications (26). Average intra-and inter-assay CV were 9.1 and 11.4%, respectively, for 3 assays.…”
Section: Methodsmentioning
confidence: 99%